2015
DOI: 10.1021/acs.energyfuels.5b00058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO2 Exposure on High-Pressure Methane and CO2 Adsorption on Various Rank Coals: Implications for CO2 Sequestration in Coal Seams

Abstract: There exist complex interactions between coal and CO 2 during the process of CO 2 sequestration in coal seams with enhanced coalbed methane recovery (CO 2 -ECBM). This work concentrated on the influence of CO 2 exposure on highpressure methane and CO 2 (up to 10 MPa) adsorption behavior of three types of bituminous coal and one type of anthracite. The possible mechanism of the dependence of CO 2 exposure on adsorption performance of coal was also provided. The results indicate that the maximum methane adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 68 publications
5
91
1
Order By: Relevance
“…However, the storage potential of CO 2 in coal beds is not as large as in salt formations or oil reservoirs, moreover, the CO 2 -ECBM technology is still at the pilot projects stage [46]. For example, some issues related to the behavior of methane and CO 2 at ultra-high pressures are not well studied yet [47]. These factors are a barrier to the implementation of the ECBM technology chain.…”
Section: Ccs Technological Chainsmentioning
confidence: 99%
“…However, the storage potential of CO 2 in coal beds is not as large as in salt formations or oil reservoirs, moreover, the CO 2 -ECBM technology is still at the pilot projects stage [46]. For example, some issues related to the behavior of methane and CO 2 at ultra-high pressures are not well studied yet [47]. These factors are a barrier to the implementation of the ECBM technology chain.…”
Section: Ccs Technological Chainsmentioning
confidence: 99%
“…Because CO 2 is a non-polar molecule, SC-CO 2 was used in the experiment to extract coal with the result that some compounds in the matrix pores or fractures can be extracted by SC-CO 2 and flow from the seepage channel along with air (Zhang et al, 2013). In this process, emphases should be given to compounds extracted by SC-CO 2 , which may cause environmental issues needing special attention on practical enhanced coal bed methane (ECBM) projects (Wang et al, 2015). Moreover, it has been proven that major components of volatile constituents that contain types of hydrocarbons, existing in the pore mouths or necks, cause a negative effect on the connectivity of pore structure (Bae et al, 2009;Nguyen and Bhatia, 2007).…”
Section: Ftir Analysismentioning
confidence: 99%
“…The decrease of micropores after SC-CO 2 treatment can be explained by the effect of adsorption-induced deformation in pores, which may lead to the expansion of micropores with increasing CO 2 pressure (Yang et al, 2011). Previous studies have shown that the extraction effect of SC-CO 2 causes a decline in the roughness degree of coal surface, and the effect is to transform smaller pores into larger pores (Gathitu et al, 2009;Wang et al, 2015;Zhang et al, 2013). The total pore volume and porosity of coal, as shown in Table 3, increased moderately after SC-CO 2 treatment.…”
Section: Further Analysis On Pore Structuresmentioning
confidence: 99%
“…China's energy structure is characterized by rich coal reserve, and meager oil and gas reserves . As a result, coal and coal‐bed methane (CBM) play an important role in its energy supply .…”
Section: Introductionmentioning
confidence: 99%